THE USE OF PICTURE SERIES IN TEACHING WRITING RECOUNT TEXT - Irfan Taofik, - (2019)
This study was aimed to investigate the use of picture series in teaching writing recount text and the students' response to it. This study employed qualitative research in form of teacher as researcher in which one class of grade ninth students at one junior high school in Bandung was chosen as the research site. Classroom observation, interview, and students' samples of writing were used as the instruments to collect the data. The findings revealed that the use of picture series facilitated teacher and students to carry out all the strategies in teaching recount text. The results showed that the use of picture series significantly assist the students to improve their vocabulary mastery. Moreover, it also helped the students to gain new ideas and arrange them in several sentences chronologically by following the sequence of the pictures. In addition, the use of picture series created fun and exciting teaching and learning environment, and activated the students' enthusiasm and activeness during classroom activity. Based on the findings, it is recommended that selecting appropriate pictures and developing appropriate classroom instruction may contribute to achieve the goals in teaching and learning recount text. Penelitian ini bertujuan untuk menginvestigasi penggunaan gambar seri dalam pembelajaran menulis teks recount dan tanggapan siswa terhadap media tersebut. Penelitian ini menggunakan penelitian kualitatif dalam bentuk teacher-as-researcher dimana satu kelas dari kelas 9 di salah satu sekolah menengah pertama di kota Bandung dipilih menjadi target penelitian. Observasi kelas, interview, dan contoh tulisan siswa digunakan sebagai instrumen dalam pengumpulan data. Temuan yang didapat bahwa penggunaan gambar seri memfasilitasi guru dan siswa memeroleh strategi dalam pembelajaran teks recount. Hasilnya menunjukan bahwa peggunaan gambar seri secara signifikan membantu siswa dalam meningkatkan pengetahuan kosakata yang mereka miliki. Selain itu, gambar seri juga membantu siswa untuk memeroleh ide-ide baru dan merancangnya ke dalam beberapa kalimat secara berurutan dengan mengikuti urutan gambar serinya. Sebagai tambahan, penggunaan gambar seri mencipatakan suasana belajar yang menyenangkan, dan mengaktifkan keantusiasa dan keaktifan siswa dalam aktivitas kelas. Berdasarkan temuan yang ada, direkomendasikan bahwa pemilihan gambar yang sesuai dan pengembangan instruksi kelas yang tepat dapat membantu pencapaian tujuan dalam pembelajaran teks recount.